MODEL OF INTANGIBLE HERITAGE CURATION OF THE CINA BENTENG COMMUNITY: A PRESERVATION STUDY AT BOEN TEK BIO - Saputra, Dwi Fajar (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2025)
The preservation of intangible cultural heritage plays a crucial role in maintaining the continuity of community identity amid modernization and social change. This study aims to analyze the community curation model applied by the Boen Tek Bio Association in sustaining the traditions, rituals, oral histories, and cultural expressions of the Cina Benteng community in Tangerang, Indonesia. Using a qualitative approach and case study method, data were collected through structured interviews, participatory observations, and document analysis. Thematic analysis was employed to identify patterns of curation, community participation dynamics, and factors influencing the sustainability of intangible cultural practices. The findings reveal that the curation of intangible heritage at Boen Tek Bio is conducted through the preservation of traditional rituals such as Gotong Toapekong and Peh Cun, the transmission of mythological stories, and the revitalization of traditional performing arts such as folk songs with Chinese-Malay influences. Active community involvement across generations, organizational support structures, and the limited adaptation to digital technology are key factors in maintaining these traditions. The main challenges identified include the lack of intergenerational cultural knowledge transfer and the decreasing interest among younger generations due to modernization. This study underscores the importance of participatory and community-based curation models in preserving intangible cultural heritage and highlights the potential of developing digital curation strategies as an adaptive response for the future.